Chamber music; a setting of five poems / by James Joyce. - Smith, Leland C.; Joyce, James 1882-1941. Chamber music; Renzi, Dorothy; Schwartz, Nathan (S.l. Fantasy 5010, 1959)
Contains settings of no. 1, 6, 8, 25, and 28 in Joyce's Chamber music.
Program notes by Alfred Frankenstein on slipcase
With : Smith, L.C. Trio, strings -- Denny, William. Partita, organ.
Dorothy Renzi, soprano; Nathan Schwartz, piano
Keywords: Song cycles; Songs (High voice) with piano